2023
DOI: 10.1128/mbio.02502-22
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Stability Emerges at the Level of Strains in the Human Gut Microbiome

Abstract: To date, there has been an intense focus on the ecological dynamics of the human gut microbiome at the species level. However, there is considerable genetic diversity within species at the strain level, and these intraspecific differences can have important phenotypic effects on the host, impacting the ability to digest certain foods and metabolize drugs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 55 publications
(127 reference statements)
2
17
0
Order By: Relevance
“…S1). Combined with the overwhelming stationarity of microbial abundance trajectories within healthy individuals not undergoing major lifestyle changes 15,32,33 , these results support our assertion that dietary patterns are largely stable over weeks-to-months and stool samples provide stable, steady-state population abundance estimates of abundant gut commensal bacteria.…”
Section: Characterizing the Relationships Between Gut Commensal Popul...supporting
confidence: 77%
See 2 more Smart Citations
“…S1). Combined with the overwhelming stationarity of microbial abundance trajectories within healthy individuals not undergoing major lifestyle changes 15,32,33 , these results support our assertion that dietary patterns are largely stable over weeks-to-months and stool samples provide stable, steady-state population abundance estimates of abundant gut commensal bacteria.…”
Section: Characterizing the Relationships Between Gut Commensal Popul...supporting
confidence: 77%
“…1-2). Thus, as prior work has indicated 15,32 , bacterial taxa in the gut have stable average population sizes, which likely represent steady-state endpoints of internal dynamics (Figs. 1-2).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recent results suggest that ecological dynamics starts to decouple at much finer phylogenetic resolutions [54]. Moreover, strains seem to still obey the three macroecological laws of variation and diversity valid at species level [55]. These results leave open the question of how ecological forces shape the variation of community composition at finer phylogenetic scales.…”
Section: Discussionmentioning
confidence: 99%
“…With our coarse-graining procedures established, we begin our macroecological investigation. Recent efforts have found that the distribution of abundances of a given taxon maintains a consistent statistically similar form across independent sites and time, a pattern known as the Abundance Fluctuation Distribution [3739, 43, 44]. By coarse-graining empirical AFDs and rescaling them by their mean and variance (i.e., standard score), we see that AFDs from the human gut microbiome retain their shape across phylogenetic scales (Fig.…”
Section: Resultsmentioning
confidence: 81%